Point-to-point conditioning of potassium dihydrogen phosphate (KDP) crystals combining sub-nanosecond and nanosecond ultraviolet lasers. (11th April 2019) - Li, Xiaofang; Wang, Bo; Li, Dazhen; Yang, Houwen; Cheng, Wenyong
Abstract: Laser-induced damage in potassium dihydrogen phosphate (KH2 PO4 or KDP) crystals is a key limitation to inertial confinement fusion laser driver systems. To increase the laser damage resistance of KDP crystals, multi-parametric experiments with different fluence steps, shot numbers, starting fluences and pulse widths have been conducted to explore an optimum laser conditioning procedure. By employing a sub-nanosecond (sub-ns) laser and nanosecond (ns) laser collinear system at 355 nm, point-to-point conditioning and damage threshold testing of the KDP crystals were investigated. It is verified that conditioning by combining sub-ns and ns ultraviolet lasers can increase the laser-induced damage threshold of KDP crystals more efficiently. Thus, an optimized conditioning process combining sub-ns and ns lasers is proposed: first, irradiation with a sub-damage-threshold sub-ns laser is done to facilitate the recombination of conduction electrons and valence belt cavities; then, ns laser conditioning is performed to help with the regrowth of inclusions, plus the decomposition and regeneration of lattice structures.